Structural model of anxiety disorders based on corona anxiety, mental health and the level of health concern with the mediating role of coping strategies in pregnant women - Angazi, Farzaneh; Hosseini, Saeedeh; Arefi, Mokhtar; Kakabraei, Keyvan (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The current research aims to present a structural model of anxiety disorders based on COVID-19 anxiety with the mediating role of coping strategies in pregnant women. Methods: This study is applied in terms of its objective, and descriptive-correlational and structural equation modeling in terms of its implementation. Data collection methods included both library and field research. In the field research, questionnaires were used to collect necessary data, including the Generalized Anxiety Disorder (GAD-13) questionnaire by Spitzer et al. (2006), the COVID-19 Anxiety questionnaire by Alipour et al. (2019), and Lazarus and Folkman’s (1988) coping strategies. SPSS22 and AMOS software were utilized for data analysis. Results: The results indicated that anxiety disorders can be predicted based on COVID-19 anxiety (p<0.01). Additionally, coping strategies were found to play a mediating role in the relationship between anxiety disorders and COVID-19 anxiety (p<0.01). The study also revealed a significant association between anxiety disorders or COVID-19 anxiety and the mediating role of coping strategies in pregnant women (p<0.01). Conclusion: Therefore, it can be concluded that anxiety disorders in pregnant women can be predicted by COVID-19 anxiety with the mediation of coping strategies.